Mengembangkan Motorik Kasar Aud Dengan Bermain Permainan Tradisional - Eka Aditiya Agustina; Syifa Nadya Salsabila Agatha; Novita Widiyaningrum (Program Studi Pendidikan Islam Anak Usia Dini, 2022)
Motor development is an aspect that needs to be considered, one of which is its development in early childhood. Motor development is often a benchmark as evidence that children are growing and developing well. Motor development is a development related to gross and smooth muscles. Gross muscles or what can be called large muscles are body muscles composed of striated muscles that have the function of carrying out activities controlled by the brain. To develop gross motor muscles each can be done by applying traditional games that can make the child's gross motor develop. There are several traditional games that can develop gross motor muscles in children including clogs, gobak sodor, and dancing. Forms of games that prioritize running, jumping, and turning are included in gross motor skills. This often happens in early childhood, because the world of play is very closely related to the development of early childhood today.